Handbook on the physics and chemistry of rare earths : including actinides. - Bunzli, J.-C. G., 1944- (ISSN, 2021)
Handbook on the Physics and Chemistry of Rare Earths: Including Actinides, Volume 59, presents the latest release in this continuous series that covers all aspects of rare earth science, including chemistry, life sciences, materials science and physics.